Addressing Health Equity in Cost-Effectiveness Analysis: A Review of Distributional and Extended Cost-Effectiveness Analysis - Lewis, Ian Storm (Department of Public Health and Family Medicine, 2022)
Background Equity is rarely included in health economic evaluations, partly because the techniques for addressing equity have been inadequate. Since 2013 health economists have developed two competing health economic technologies: distributional costeffectiveness analysis (DCEA) and extended cost-effectiveness analysis (ECEA). Both technologies represent a significant advance, and each provides a framework to address equity considerations in cost-effectiveness analysis. Methods A scoping literature review was used to identify and synthesise the relevant literature on incorporating equity concerns into economic evaluations. A second focused review identified literature which discussed or applied DCEA and ECEA. Key themes in the literature were identified using NVivo qualitative data analysis software. Results The review revealed three key areas of difference between DCEA and ECEA: First, the analysis of trade-offs between improving health and reducing inequity; second, the analysis of financial impacts of health policies; and third, the incorporation of opportunity costs. ECEA can analyse financial risk protection while DCEA can analyse opportunity costs and trade-offs between improving equity and reducing health. ECEA is designed for low- and middle-income countries, whereas DCEA is better suited to developed health systems such as the National Health Service in the United Kingdom. To date, there have been 27 studies using ECEA and five studies using DCEA. Future developments for DCEA and ECEA include incorporating alternative methods to simplify the data requirements for the techniques, providing methods to assist decision makers to clarify their equity concerns, and improving the presentation of outcomes to make them accessible to non-specialists. Conclusions DCEA and ECEA are both economic frameworks which address equity considerations in cost-effectiveness analysis. This study examines and compares these two techniques in order to assist policymakers and decision makers to determine which of the two methods is best able to address their specific needs for their particular circumstances.